Напрями наукової діяльності науково-дослідного інституту фізики Одеського державного університету за радянських часів - Філіпова, О.І. (Центр пам'яткознавства НАН України та Українського товариства охорони пам'яток історії та культури, 2009)
Статья посвящена советскому периоду научной деятельности НИИ физики Одесского Национального университета им. И. И. Мечникова. В статье проанализирован вклад одесских физиков в развитие теории научной фотографии. Article is devoted to the Soviet period of scientific activity of scientific research institute of physics of the Odessa National university of I.I.Mechnikov. The contribution of the Odessa physics in the theory of scientific photography is analysed in this article.